Pharmaceutical calculations for pharmacy technicans : - Moini, Jahangir (Thomson Delmar Learning, 2007)
This book focuses on dosage calculations and basic math skills: from simple addition and subtraction to formulas used in dosage calculations to business math concepts. Accuracy in calculations will guide the Pharmacy Technician in the prevention of medication errors